The Link Between Inflammation and Cancer Wounds that do not heal - Dalgleish, Angus G.; Haefner, Burkhard; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
The transcription factor NF-kB has long been known to play a central role in the immune system by regulating the expression of key genes. Moreover, activation of this transcription factor helps a wide variety of cell types survive damage induced by pro-apoptotic stimuli. Owing to its critical role in the regulation of pro-inflammatory genes, NF-kB has long been regarded as a promising target for the discovery of anti-inflammatory drugs. More recently, NF-kB has emerged as a major culprit in a variety of human cancers mainly due to its ability to protect transformed cells from apoptosis. This finding should not have come as a surprise since there exists a link between inflammation and many types of cancer which was already suggested by Galen and later demonstrated by Virchow. This link, of crucial importance for the design of novel strategies for cancer treatment, is the topic of this book. Series Editor Cover Comments: "Inflammation is a known risk factor for a number of cancers. In this text, experts discuss the pathophysiology and molecular alterations that link these two processes. Potential therapeutics and preventive strategies are discussed." Steven T. Rosen, M.D. Series Editor.
Inflammation and Cancer -- Chronic Inflammation and Pathogenesis of GI and Pancreatic Cancers -- Cytokines, NF-?B, Microenvironment, Intestinal Inflammation and Cancer -- Regulation if NF-?B Transcriptional Activity -- The Role of Immune Cells in the Tumor Microenvironment -- Tumor-Microenvironment Interactions -- CD95L/FasL and TRAIL in Tumour Surveillance and Cancer Therapy -- Infection & Neoplastic Growth 101 -- Cytokines as Mediators and Targets for Cancer Cachexia -- Targeting NF-?B in Anticancer Adjunctive Chemotherapy.
Keywords: Medicine; Cancer research; Laboratory medicine; Oncology; Medicine & Public Health; Oncology; Cancer Research; Laboratory Medicine; Electronic books